Problem solving for engineers - Carmichael, D. G., 1948- (Boca Raton : Taylor & Francis, 2013)
'This book takes a systematic approach to problem definition, generation of alternative solutions, analysis, and selection of the preferred solution. The book introduces some fundamental terms needed to think systematically and undertake systematic problem solving. It covers both individual and group problem solving. Selection of the preferred solution involves decision making, and fundamental concepts of decision making are introduced, including decision making in the presence of multiple criteria and uncertainty. The treatment embodies decision making for sustainability, with its blend of economics, social and environmental considerations. It also identifies and embodies the specific problem solving of management and planning'--
Includes bibliographical references (pages 403-405) and index.
Keywords: Project management; Engineering -- Decision making; Problem solving